2009
DOI: 10.1590/s0365-05962009000500004
|View full text |Cite
|
Sign up to set email alerts
|

Expressão de marcadores de proliferação celular e apoptose no carcinoma espinocelular de pele e ceratose actínica

Abstract: Resumo: FUNDAMENTOS: O câncer de pele é o mais frequente tipo de câncer humano e mostra aumento de sua incidência. Em muitos casos, antes do surgimento do carcinoma, instala-se uma lesão precursora, ceratose actínica, podendo evoluir para carcinoma espinocelular. Estudos buscam determinar os parâmetros com significado prognóstico na predição daqueles tumores que terão comportamento mais agressivo. OBJETIVO: Avaliar a expressão dos marcadores de proliferação celular (PCNA, Ki-67) e apoptose (p53, Bcl-2), em por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 11 publications
0
12
0
1
Order By: Relevance
“…Some authors evaluated the expression of PCNA, Ki-67, p53 and bcl-2 in patients with squamous skin carcinoma (n=10) and actinic keratosis (n=10), and confirmed the absence of Ki-67 expression in two cases, confirming the variability in this marker's immunoreactivity 18 . However, it is interesting to note that in several studies the Ki-67 presents a tendency to strong direct correlation with the lesion malignancy degree, being valuable as a prognostic predictor 17,18 .…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Some authors evaluated the expression of PCNA, Ki-67, p53 and bcl-2 in patients with squamous skin carcinoma (n=10) and actinic keratosis (n=10), and confirmed the absence of Ki-67 expression in two cases, confirming the variability in this marker's immunoreactivity 18 . However, it is interesting to note that in several studies the Ki-67 presents a tendency to strong direct correlation with the lesion malignancy degree, being valuable as a prognostic predictor 17,18 .…”
Section: Discussionmentioning
confidence: 81%
“…The Ki-67 immunoreactivity relates to evidence of cell proliferation, so that it is expressed in all cell cycle phases but G0, in which cells are quiescent 18 . According to Sousa et al 19 , immunohistochemical analysis of this marker is an effective method for assessing the human malignancies growth fraction, providing valuable information about prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…al, 2006). Studies by DORNELAS et al (2009) suggested that the prolonged stay of the cell in the G1 phase of the cycle may lead it to apoptosis, and also that the inappropriate output of the G1 phase forces the p53 protein to suppress cell growth more pronouncedly. Figure 4 shows the important role of p53 in maintaining the genome integrity, acting systematically against injuries to the cell genetic material.…”
Section: Mechanisms Of Action Of P53 In Neoplasiasmentioning
confidence: 99%
“…2 The lethality of nonmelanoma skin cancer is considered low; however, in some cases in which diagnosis is delayed, this cancer may lead to ulcerations and severe physical deformity. 2,3 There is, almost certainly, considerable under-registration as a result of under-diagnosis and also because prognosis is excellent with this type of neoplasia and the likelihood of complete cure is high if the condition is treated adequately and opportunely. 2 The majority of skin cancers result from excess sun exposure.…”
Section: Introductionmentioning
confidence: 99%